(untitled) (Res Medica, 2014)
Introduction: This study is a replication of Murphy and Zajonc (1993), Jenner (2000), and Chalmers (2000) in order to test the affective priming hypothesis. Method: University of Edinburgh students were shown short exposures of faces showing emotional expressions (affective primes) ranging from 12.5 ms to 44 ms. This was followed by a mask and then a neutral face which they were asked to rate for likeability on a scale from 1 to 5. Their recognition of the emotional face was tested by a separate experiment at each exposure time. Results: No affective priming effect was found either when there was no recognition of the affective prime above chance or when recognition was significantly above chance. However, the results do suggest that recognition of the polarity of emotion shown occurs before the recognition of the specific emotion. Conclusion: This study does not support Murphy and Zajonc’s (1993) affective priming hypothesis. The findings do suggest that the primary recognition of faces may be towards a positive/negative judgement with the identification of the specific emotion shown occurring later.